MENANAMKAN PHBS PADA ANAK USIA SEKOLAH : EDUKASI DAN PRAKTIK CUCI TANGAN ENAM LANGKAH BAGI SISWA FASE A DI MIN X PADANG - Englardi, Noly; Nia Syafriani; Abri Madoni; Monna Widyastuti (JURNAL PENGABDIAN KEPADA MASYARAKAT SISTHANA, 2025)
Often clean and healthy living behavior is considered trivial and rarely noticed will threaten health, especially at school age which is an age that is vulnerable to disease because of the behavior and habits they do in the environment, especially at school. The purpose of this community service is to increase awareness and stimulate school-age children to be able to instill PHBS, especially washing hands in six steps properly and correctly. The method used is providing education or counseling. The results of providing this education are that students are able to explain the definition, purpose, benefits, time, and practice the six-step hand washing method properly and correctly. From this community service activity, it can be concluded that the education and practice of hand washing that has been carried out has succeeded in helping school-age children understand one of the PHBS methods.